2013
DOI: 10.1146/annurev-physiol-030212-183737
|View full text |Cite
|
Sign up to set email alerts
|

Functions of MicroRNAs in Cardiovascular Biology and Disease

Abstract: In 1993, lin-4 was discovered as a critical modulator of temporal development in Caenorhabditis elegans and, most notably, as the first in the class of small, single-stranded noncoding RNAs now defined as microRNAs (miRNAs). Another eight years elapsed before miRNA expression was detected in mammalian cells. Since then, explosive advancements in the field of miRNA biology have elucidated the basic mechanism of miRNA biogenesis, regulation, and gene-regulatory function. The discovery of this new class of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
153
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(155 citation statements)
references
References 112 publications
0
153
0
2
Order By: Relevance
“…1 MiRNAs play a role in regulating various biological processes including embryogenesis, cell proliferation and differentiation, apoptosis or tumorigenesis. 2 In the cardiovascular system, miRNAs control cardiomyocyte growth and contractility, the development and maintenance of cardiac rhythm, plaque formation, lipid metabolism and angiogenesis. [2][3][4][5] Altered miRNA expression can be found in the blood of patients with various cardiovascular diseases, which makes them attractive candidates for noninvasive biomarkers.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1 MiRNAs play a role in regulating various biological processes including embryogenesis, cell proliferation and differentiation, apoptosis or tumorigenesis. 2 In the cardiovascular system, miRNAs control cardiomyocyte growth and contractility, the development and maintenance of cardiac rhythm, plaque formation, lipid metabolism and angiogenesis. [2][3][4][5] Altered miRNA expression can be found in the blood of patients with various cardiovascular diseases, which makes them attractive candidates for noninvasive biomarkers.…”
mentioning
confidence: 99%
“…2 In the cardiovascular system, miRNAs control cardiomyocyte growth and contractility, the development and maintenance of cardiac rhythm, plaque formation, lipid metabolism and angiogenesis. [2][3][4][5] Altered miRNA expression can be found in the blood of patients with various cardiovascular diseases, which makes them attractive candidates for noninvasive biomarkers. 6,7 It has been estimated that miRNAs control the activity of 30-50% of protein-coding genes.…”
mentioning
confidence: 99%
“…miRNAs suppress target transcription and translation by binding to the 3'-untranslated regions (3'UTRs) of target mRNAs. These small endogenous silencers can regulate diverse biological processes, such as proliferation, apoptosis, angiogenesis, cholesterol metabolism and inflammation [7] . Increasing evidence indicates that miRNAs play important roles in the development of AS [12] .…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) constitute a broad class of short noncoding RNAs that have been extensively studied in the context of cancer. Recently, increasing evidence has indicated that miRNAs are involved in the development of AS [7] . miRNAs can modulate the expression of various cytokines or inflammatory molecules by binding to the complementary target sites in the 3'untranslated regions (3'UTR) of mRNA sequences and inducing mRNA degradation or translational repression.…”
Section: Introductionmentioning
confidence: 99%
“…There have been over 1,000 annotated miRNAs in humans, and due to the potential to target multiple mRNAs by each miRNA, it is speculated that as much as 60% of mammalian genes are affected by miRNAs [3,4]. Thus abnormal changes in miRNA expression can cause dysregulation of important biological pathways, and are involved in many diseases such as cancers and cardiovascular disease [5][6][7]. Therefore determination of the target mRNAs of the variety of miRNAs will help understand the development of these diseases.…”
Section: Introductionmentioning
confidence: 99%